2020
DOI: 10.1155/2020/9672673
|View full text |Cite
|
Sign up to set email alerts
|

MEST Regulates the Stemness of Human Periodontal Ligament Stem Cells

Abstract: Periodontal ligament (PDL) stem cells (PDLSCs) have been reported as a useful cell source for periodontal tissue regeneration. However, one of the issues is the difficulty of obtaining a sufficient number of PDLSCs for clinical application because very few PDLSCs can be isolated from PDL tissue of donors. Therefore, we aimed to identify a specific factor that converts human PDL cells into stem-like cells. In this study, microarray analysis comparing the gene profiles of human PDLSC lines (2-14 and 2-23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
0
11
1
Order By: Relevance
“…Of relevance, Mest1 was the only gene with functional regulatory stemness property ( Hasegawa et al, 2020 ), identified from the analysis of genes downregulated in ex vivo skeletal stem/progenitor cells, and interestingly Copg2 a member of mouse imprinted genes linked to Mest1 was also downregulated ( Lee et al, 2000 ; Figure 5C ). Along with aforementioned, several genes encoding cell-adhesion proteins were also noticed, among them were Spon2 ( Zhang et al, 2018 ), Smoc2 ( Morkmued et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of relevance, Mest1 was the only gene with functional regulatory stemness property ( Hasegawa et al, 2020 ), identified from the analysis of genes downregulated in ex vivo skeletal stem/progenitor cells, and interestingly Copg2 a member of mouse imprinted genes linked to Mest1 was also downregulated ( Lee et al, 2000 ; Figure 5C ). Along with aforementioned, several genes encoding cell-adhesion proteins were also noticed, among them were Spon2 ( Zhang et al, 2018 ), Smoc2 ( Morkmued et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Those characteristics of GF(IL‐4) were reinforced by the new identification of genes related to tissue development or ECM components such as MEST, TNC, POSTN, TGM2, and COL3A. MEST is related to the stemness of human periodontal ligament stem cells, 32 and the transglutaminase 2 coded by TGM2 stabilizes ECM proteins by cross‐linking, which makes them highly resistant to protease degradation 33 . In contrast, the immune response inhibiting characteristics of GF(IL‐4) were newly defined through our finding that IL‐4 down‐regulates genes associated with the immune response, such as CXCL10, CXCL8, LILRB4, RSAD2, and TNFSF18, LILRB4 is associated with antigen capture and presentation, 34 and the protein coded by RSAD2 activates and differentiates T cells 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Hasegawa et al . reported that the overexpression of human MEST enhanced the expression of stem cell markers and the multi-differentiation capacity, and knockdown of MEST inhibited the expression of stem cell markers and promoted differentiation of periodontal ligament stem cells [ 29 ]. In mouse adipose tissue, the expression level of Mest is decreased during the lactation period, when adipocyte differentiation and maturation should become more prolific [ 7 ].…”
Section: Discussionmentioning
confidence: 99%